Characteristics of lightning electromagnetic fields produced by Antarctica storms - Ahmad, Mohd Riduan; Mohammad, Sulaiman Ali; Abdullah, Mardina; Shamsul Baharin, Shamsul Ammar; Yusop, Norbayah; Park, Sangjong; Lu, Gaopeng; Cooray, Vernon (MDPI, 2022)
This paper presents the temporal characteristics of electromagnetic fields produced by cloud-to-ground (CG) lightning flashes associated with Antarctica storms. A total of 51 positive CG (+CG) and 103 negative CG (−CG) flashes have been recorded by a magnetic direction finder (MDF) sensor in King Sejong Station, King George Island. In total, 47 positive and 107 negative return strokes were located, ranges from 32 to 569 km. All CG flashes were detected to occur over the ocean. The return strokes characteristics include the observations of slow front, fast rising, rise time, and pulse duration with geometric mean values of 3.2, 0.53, 3.21, 13.12, and 67.09 µs for +CG flashes, while 3.9, 0.57, 3.72, 20.75, and 69.86 µs for −CG flashes, respectively. Additionally, the average peak currents of +CG and −CG flashes were 4.13 kA and 3.14 kA, respectively. The temporal characteristics of the return strokes of Antarctica storms are comparable to other geographical regions. The smaller peak currents might be due to small magnitude of Antarctica cloud charges when compared to other geographical regions.